Identification of Alternative Conceptions of Genetics held by Senior School Students in Ilorin, Nigeria, Using a Three-Tier Diagnostic Test - Ahmed, Mulkah Adebisi; Opatola, Yetunde Morenike; Yahaya, Lukman; Sulaiman, Musa Muhammed (NIU Journal of Social Sciences, 2018)
Students bring to lessons a lot of pre-existing (alternative) conceptions about scientiï¬c phenomena that can interfere with studentsâ€™ learning of correct scientiï¬c concepts (Gurel, Erylimaz & McDermott, 2015). Alternative conceptions are false or non-scientific beliefs held by students on a specific concept or phenomenon, which may be caused by their misunderstanding of other subjects or gained from their earlier experiences (Abdulwali & Alshaya, 2012). Alternative conceptions related to biology concepts are widely spread among students at every level of educational ladder and it represents a real barrier to studentsâ€™ understanding of biology (Bello, Bello & Abimbola, 2016).  Alternative conceptions have been reported in most topics (genetics, ecology, respiration and photosynthesis) and across several educational levels (Taber, 2009).